“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.
Number: 6

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

Resources for Future in a Caring Economy - Gassner, Franz (Menschenrechte und Gerechtigkeit als bleibende Aufgaben, 2020)

Journalism Ethics and the Common Good: The Formation of Values and Virtues for Just and Harmonious Societies - Gassner, Franz; Simoes, José Manuel (Disentangled Vision On Higher Education: Preparing The Generation Next, 2022)